Rekonstruksi Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Berbasis Google Sites Sebagai Upaya Penguatan Karakter Profil Pelajar Pancasila di SMA Negeri 1 Baureno Bojonegoro - Agus Moh. Sholahuddin; Anggun Wahyu Sulistya Alyasinda (Politeknik Kampar, 2023)
Reconstruction of the world order of education is urgently needed, in order to be able to maximize technological developments. Millennials will generally be more interested in things that have visual components or platforms that are connected to the internet. Learning Islamic religious education and morals is one area that needs reconstruction because so far it has been normative and dogmatic. With the latest learning, namely strengthening the character of the Pancasila student profile so that it is sustainable with the formation of student character with Pancasila values ??through certain projects. In addition, students can take part in learning Islamic religious education and morals according to the era of the industrial revolution 4.0 through google sites. This study uses a qualitative approach to phenomenology. Data collection was carried out using observation techniques, interviews with 9 sources, and documentation. Data analysis techniques include data reduction, data display, and conclusions. Based on the research conducted, the following results were obtained: (1) Reconstruction of learning Islamic religious education and morals based on Google sites at SMA Negeri 1 Baureno Bojonegoro went well. (2) Efforts to strengthen the profile character of Pancasila students through the reconstruction of learning Islamic religious education and manners based on Google sites at SMA Negeri 1 Baureno Bojonegoro are in accordance with the six main characteristics of Pancasila student profiles.